EGFR-targeted liposomal nanohybrid cerasomes: theranostic function and immune checkpoint inhibition in a mouse model of colorectal cancer - Li, Yuan; Du, Yang; Liang, Xiaolong; Sun, Ting; Xue, Huadan; Tian, Jie; Jin, Zhengyu (Nanoscale, 2018)
Epidermal growth factor receptor (EGFR) is a major target for the treatment of colorectal cancers (CRCs), and programmed death ligand-1 (PD-L1) is an attractive target for CRC immunotherapy. Herein, we report the synthesis of porphyrin-containing liposomal nanohybrid cerasomes decorated with cetuximab, an anti-EGFR antibody, and conjugated with IRDye800CW and MRI contrast DOTA-Gd, to enable in vivo tumor detection and photodynamic therapy (PDT). Moreover, PD-L1 was added for adjuvant therapy. The antitumor efficacy of PDT combined with PD-L1 immunotherapy was assessed. EGFR-targeted nanoparticles showed the targeted imaging of tumors. EGFR-targeted PDT combined with PD-L1 immunotherapy was more effective against tumor growth than simultaneous albeit nontargeted nanoparticle delivery with laser irradiation plus PD-L1 immunotherapy. Thus, EGFR-targeted nanoparticles exhibited significant potential toward dual-modality imaging-guided precise PDT, combined with immunotherapy. The epidermal growth factor receptor (EGFR) is a major target for the treatment of colorectal cancers (CRCs), and programmed death ligand-1 (PD-L1) is an attractive target for CRC immunotherapy.